2018
DOI: 10.1177/2333393618792076
|View full text |Cite
|
Sign up to set email alerts
|

A Relational Perspective on Social Support Between Bereaved and Their Networks After Terror: A Qualitative Study

Abstract: The aim of this study is to increase the understanding of social network support after traumatic deaths and, by demonstrating the complexities of such encounters, to highlight whether such support may be totally beneficial. A phenomenological dynamic and relational perspective was applied to 22 in-depth interviews with parents bereaved as a result of the 2011 terror attack in Norway. Three main themes were identified in respect of interactional support processes: (a) valued support, (b) stressful experiences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
(49 reference statements)
5
22
0
1
Order By: Relevance
“…Openness, an assertion of personal needs, involves educating others as to how to support them (K. Dyregrov & Dyregrov, 2008 , p. 118) and can help the bereaved deal with the overload ( Stroebe & Schut, 2016 ). In line with other studies of unnatural deaths (K. Dyregrov & Dyregrov, 2008 ; K. Dyregrov et al., 2018 ; Feigelman et al., 2020 ), there are good reasons to argue here that proactive bereaved persons can help people in their social networks to take the perhaps difficult step to talk about DRD. Social networks therefore need to be informed of their potential role through listening with respect and through empathy.…”
Section: Discussionsupporting
confidence: 82%
“…Openness, an assertion of personal needs, involves educating others as to how to support them (K. Dyregrov & Dyregrov, 2008 , p. 118) and can help the bereaved deal with the overload ( Stroebe & Schut, 2016 ). In line with other studies of unnatural deaths (K. Dyregrov & Dyregrov, 2008 ; K. Dyregrov et al., 2018 ; Feigelman et al., 2020 ), there are good reasons to argue here that proactive bereaved persons can help people in their social networks to take the perhaps difficult step to talk about DRD. Social networks therefore need to be informed of their potential role through listening with respect and through empathy.…”
Section: Discussionsupporting
confidence: 82%
“…In a Norwegian qualitative study of people bereaved by suicide, accidental death, and sudden infant death syndrome, participants reported that because these were unusual deaths, others were unsure about what to say or how to offer support [24]. This is contrasted with a Norwegian qualitative study describing the experiences of people bereaved by terrorist attack, in which public outrage appeared to fuel an outpouring of support [25]. Whilst this did not preclude experiences of others’ avoidance and social awkwardness, it was comforting for participants to know that other offers of support were available.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a number of Katrina-related trauma exposures indicated relational stressors and losses, which could impact both perceived social support and PTG Full Scale, and perhaps the relationship between them as well. Indeed, research has shown that experiencing bereavement through sudden deaths are more likely to have barriers in accessing support from their social networks and perceived less social support overall (Dyregrov et al, 2018; Frost et al, 2017). It is also possible that the associations between changes in perceived social support is not a strong driver of PTG Full Scale, particularly when social networks continue to change within the postdisaster period.…”
Section: Discussionmentioning
confidence: 99%